DEVELOPMENT AND EVALUATION OF SELF EMULSIFIED DRUG DELIVERY SYSTEM OF EMBELIN FOR THE TREATMENT OF AMOEBIASIS - LAL, BHARAT; GADEWAR, MANOJ; GARG, ARUN (International Journal of Applied Pharmaceutics, 2022)
Objective: Development and evaluation of self-emulsified drug delivery system of embelin for the treatment of amoebiasis. Methods: Self-emulsifying drug delivery systems (SEDDS) were prepared by determining the saturation solubility of embelin in different oil, surfactant and co-surfactant. Pseudo-ternary phase diagram was prepared by using chemix software for the selection of surfactant and co-surfactant ratio, and was optimized as 2:1 (Surfactant: Co-surfactant) for SEDDS. The drug was dissolved in surfactant, followed by the addition of co-surfactant and oil in a beaker. The resultant mixtures were stirred continuously by magnetic stirrer and heated at 40 °C to obtain a homogenous mixture. The prepared drug-loaded SEDD formulation was optimized on the basis of emulsification time, size, PDI, zeta potential and precipitation of drugs. Then the anti-amoebic activity of embelin and metronidazole-loaded SEDDS powder was carried out using microplate reader. Results: The optimum solubility of embelin was calculated in Capmul MCM EP as oil (37 mg/ml), Kolliphor hs 15 as surfactant (150 mg/ml) and PEG 400 as co-surfactant (19 mg/ml). The formulation F7 i.e. 70% Smix and 30% oil was estimated as optimized formulation. The different values of emblein loaded SEDDS was found to be dilution test (no sign of precipitation), centrifugation test (no sign of phase separation), globule size (Dia 217.5 nm) and PDI (108), zeta potential determination (-31.60 mV), viscosity (17.12 cps) and Eosin red confirmed the o/w type of emulsion. Moreover, the angle of repose SEDDS prepared by using Avicel 200 was found to be Θ=27.474, means flow of powder is good with drug loading capacity of 92.7 %. SEM image and in vitro drug release indicated the 99.3% drug was released from the SEDDS in 120 min. Cytotoxicity study (MTT assay) shows the Plain Drug Suspension, Embelin loaded SEDDS powder and Metronidazole exhibited 100% viability at the concentration range of 1.56-100 mmol. The anti-amoebic IC50 values of embelin, metronidazole and embelin loaded SEDDS powder was found 1.519 µmol, 1.354 µmol, 1.84 µmol and 1.35 µmol, respectively. Conclusion: Present study showed the stronger amoebicidal action of embelin may associated with some specific interaction of the active embelin with the cell wall of the parasites or with a more effective mechanism of penetration into the parasites through membrane channels.